(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper attempts to know liberal policy framework in FDI on industrial sector and its limits. Study also justifies various determinants of FDI and its advantages and specification different routes of FDI also reveal the trend in inflow of FDI from 2000 to 2017.Service sector receives the highest FDI inflows recording a total inflow of 59,476.49 US Million Dollars. The actual inflows of FDI during 2005 –2017 have been through RBI’s automatic route it accounts to 64.98 of total FDI flow.